Preliminary Observations on the Sperm Biology of (Bunnei Barbus sarpeyi, 1874) after Hormone Injection and Preservation - Al-Mukhtar, Mustafa A.; Al- Noor, Saged S.; Al-Zaidy, Faleh M. (Iraqi Journal of Aquaculture, 2022)
Observations on the sperm biology of Bunnei (Barbus sharpeyi), after hormone injection perm activity for the injected fish ranged between 85 % - 100 %. The most amazing finding was the sperm activity of the collected semen from deceased fish after one hour was 90 %, and it has the highest activity time(120 sec.), this time was higher than that for the Bunnei from Al-Therthar reservoir during spawning season. The sperm volume was very low (1- 0.4 ml). which is a characteristic of this species. The sperm concentration ranged between (25.85 - 40.69) × 109 , and it is also higher than that for Bunnei in Al-Therthar reservoir.